Video Steganography Method based on Haar DWT and Spread Spectrum Technique - Elakkiya, D.; Mahesh, Dr.K. (IJRDO -Journal of Computer Science Engineering, 2016)
In the development of the network field, the necessityfor hiding the information is more important for protecting theinformation from the third party in an open network. In order toovercome this video stegnography technique is used. It is theprofession of hiding the information which helps to conceal thesensitive data than other medium. In stegnography differentcover objects are used for video, it can be separate into imagesand audio and accommodate massive amount of secretinformation. In this proposed work, introduce the new methodfor hiding the secret data into a video file using videostegnography technique. In this technique, Haar DWT andspread spectrum to get a stego video. And obtain extractionprocedure is similar to embedding procedure vice versa. So thatthis proposed method is convenient and extracting data easilyfrom stego video.